Aldosterone Synthase Inhibitors for Cardiorenal Protection: Ready for Prime Time? - Alessio Mazzieri; Francesca Timio; Francesco Patera; Francesco Trepiccione; Mario Bonomini; Gianpaolo Reboldi (Kidney & Blood Pressure Research)
Background: Aldosterone is the principal mineralocorticoid hormone and the final effector of the renin-angiotensin-aldosterone system. This hormone is primarily synthesized by the CYP11B2 enzyme and produced by the adrenal zona glomerulosa. Through genomic and non-genomic effects, it plays an important role in cardiovascular and renal disease. To counteract aldosterone-mediated damage, steroidal mineralocorticoid receptor antagonists are recommended by international guidelines, but endocrine side effects often limit their use in a substantial proportion of patients. Conversely, nonsteroidal mineralocorticoid receptor antagonists, with an improved selectivity and safety profile, are gaining a prominent position among therapeutic pillars. However, blocking the mineralocorticoid receptors does not completely inhibit aldosterone effects because of escape mechanisms and non-genomic activity. Thus, inhibiting aldosterone synthesis could be a promising strategy to prevent aldosterone-mediated cardiorenal damage. The limited specificity for CYP11B2 and side effects due to off-target activity hampered the development of first-generation aldosterone synthase inhibitors (ASIs). Summary: The development of highly specific ASIs led to successful clinical trials in patients with resistant and uncontrolled hypertension. Additionally, a recent randomized clinical trial showed a significant benefit of ASIs in patients with chronic kidney disease and albuminuria. Key Messages: The strength of the clinical evidence collected so far is still limited, and larger outcome-based clinical trials are needed to confirm the promising role of ASIs in cardiorenal damage. Background: Aldosterone is the principal mineralocorticoid hormone and the final effector of the renin-angiotensin-aldosterone system. This hormone is primarily synthesized by the CYP11B2 enzyme and produced by the adrenal zona glomerulosa. Through genomic and non-genomic effects, it plays an important role in cardiovascular and renal disease. To counteract aldosterone-mediated damage, steroidal mineralocorticoid receptor antagonists are recommended by international guidelines, but endocrine side effects often limit their use in a substantial proportion of patients. Conversely, nonsteroidal mineralocorticoid receptor antagonists, with an improved selectivity and safety profile, are gaining a prominent position among therapeutic pillars. However, blocking the mineralocorticoid receptors does not completely inhibit aldosterone effects because of escape mechanisms and non-genomic activity. Thus, inhibiting aldosterone synthesis could be a promising strategy to prevent aldosterone-mediated cardiorenal damage. The limited specificity for CYP11B2 and side effects due to off-target activity hampered the development of first-generation aldosterone synthase inhibitors (ASIs). Summary: The development of highly specific ASIs led to successful clinical trials in patients with resistant and uncontrolled hypertension. Additionally, a recent randomized clinical trial showed a significant benefit of ASIs in patients with chronic kidney disease and albuminuria. Key Messages: The strength of the clinical evidence collected so far is still limited, and larger outcome-based clinical trials are needed to confirm the promising role of ASIs in cardiorenal damage.